Legal Protection of Creditors Against Auction Execution of Mortgage Rights Objects in Disputes - Wiguna, Ervan; Musthofa, Hanna Noviana Noer; Maskanah, Ummi (Manunggal Halim Jaya, 2025)
The execution of mortgage collateral auctions often encounters legal obstacles when the object of collateral provided by the debtor is under dispute. Such conditions pose significant challenges to the legal protection of creditors, particularly in their efforts to secure debt repayment through auction mechanisms. Disputes over the collateral frequently result in delays or even render the auction process infeasible, weakening the creditors' position as holders of mortgage rights. This study analyzes the legal protection afforded to creditors against obstacles in auction execution caused by disputes over the collateral. Furthermore, the research examines the role of legal provisions stipulated in Law No. 4 of 1996 concerning Mortgage Rights in resolving such challenges. The findings emphasize the necessity of stricter law enforcement and the establishment of effective dispute resolution mechanisms to safeguard creditors' rights, even when the mortgage collateral is subject to legal disputes.